Constructive alignment of Mother Tongue-Based Multilingual Education (MTB MLE) language policy implementation to the practices of a multilingual classroom - Gempeso, Hyra Dave Pepito; Mendez, Jubelle Dianne Solatorio (Universitas Ahmad Dahlan, 2021)
This descriptive observational study examined the implementation of Mother Tongue-Based Multilingual Education (MTB MLE) language policy to the classroom practices of a grade three multilingual classroom in the Philippines. The constructive alignment of the said language policy implementation was evaluated in terms of: (1) Mother Tongue (MT) as a subject area, examining specifically the coherence of the teaching and learning activities and assessment criteria used; and (2) MT as a medium of instruction. Findings revealed that there were discrepancies, incongruences, and insufficiencies in the administration of assessments in the alignment of MT as a subject area. These issues resulted in the underdevelopment of the four macro skills of the learners and caused misalignment of the classroom implementation to the language policy. The same is true with the implementation of MT as a medium of instruction in the classroom; however, the use of translation and code-switching of L1, L2, and L3 helped in the comprehension and participation of the students. These findings call for the attention of the policymakers and teachers for a rigorous review of the policy and its actual implementation as it significantly affects the holistic development of the students. This study further contributes to the continuous improvement of the educational system in the country particularly in the K-12 and MTB MLE implementation.